Effectiveness of Implementation of the 1974 SOLAS Convention Regarding Safety Standards at Public Ports in Batam City - Maharani Siregar, Ghea Regita; Priyo Amboro, Florianus Yudhi; Sudirman, Lu (IHSA Institute, 2025)
The International Maritime Organization (IMO) held a conference from 9 to 13 December 2002 in London, resulting in an amendment to the international convention on safety of life at sea or Safety of Life at Sea (SOLAS) 1974. This research aims to analyze the effectiveness of implementing SOLAS 1974, analyzing obstacles, and providing solutions in dealing with obstacles in the implementation of SOLAS 1974 at the Public Port in Batam City. The research objects are SCN Batam Public Harbor, BP Batam and 99 Batu Ampar Harbor. The research results were analyzed using the theory of legal effectiveness according to Soerjono Soekanto which consists of five factors, namely the legal factor itself, law enforcement factors, facilities and infrastructure factors, community factors and cultural factors which are the results of the research. From this research it can be concluded that at the SCN Public Port the facilities and infrastructure factors were found to be less effective and other factors were effective, whereas at the BP Batam and 99 Batu Ampar Ports each factor was found to be effective. The obstacle experienced by the SCN Batam Public Port in implementing SOLAS 1974 was support from the Company itself, namely the provision of facilities and infrastructure for. Meanwhile, the obstacle experienced by the BP Batam and 99 Batu Ampar Public Ports in implementing the results of the researchers' field observations was the lack of firmness in law enforcement in the field